RISK ANALYSIS OF CO EMITED FROM MOTOR VEHICLES TO PEOPLE LIVING AND DOING ACTIVITIES IN ROADSIDE (CASE STUDY: JOGJAKARTA’S MAIN STREETS) - Budihardjo, Mochamad Arief (Universitas Diponegoro, 2007)
Air pollution problems have been progressively set attention to the world specifically in industrial countries recently. This problem not only gives affect at health like emphysema, bronchitis, and other inhalation disease but also makes plants and property destruction that causing loss. Research concerning in the level of risk which is accepting by people who living and doing activities in roadside which most of air pollutants come from transportation facilities such as motor vehicles. This research focuses on CO exposure which penetrates the body through respiration. There are four steps in this research, first, hazard identification showing CO concentration in 15 sampling locations resulting highest CO concentration is equal to 17.250 µg/m3; second, exposure assessment involves population exposed that are Pedi cab worker, parking man, and cloister merchant to know CO intake each person using calculation of CO intake range from 1,0703-2,6089 mg/kg . day; third, dose-response assessment to know what people will be experiencing if exposed by CO at certain dose; fourth, risk characterization resulting that risk value/Hazard Index (HI) less than 1. This research concludes that CO concentration of most main streets in Jogjakarta do not adverse to people’s health who living and doing activities in roadside